Pengaruh Temperatur Penumbuhan terhadap Struktur Kristal dan Morfologi Film Tipis TiO2:Eu yang Ditumbuhkan dengan Metode MOCVD [The Effect of Growth Temperature on the Crystall Structure and Morphology of the Thin Film TiO2:Eu Grown with MOCVD Method] - Edy Supriyanto; Goib Wiranto; Hery Sutanto; Agus Subagio; Mikrajuddin Abdullah; Maman Budiman; Pepen Arifin; Sukirno Sukirno; Mohamad Barmawi (Jurnal Matematika & Sains, 2007)
Thin film of TiO2:Eu had been grown on an n-type Si(100) substrate using Metalorganic Chemical Vapor Deposition (MOCVD) method with titanium (IV) isopropoxide [Ti{OCH(CH3)2}4] 99.99% and europium nitrate [Eu(NO3)3.6H2O] 99.99% as the metal organic precursors. The tetrahydrofuran (THF) was used as a solvent for the precursor. X-ray Diffraction (XRD) analysis showed that the TiO2:Eu thin film grown at temperature of 450 Î¿C had crystal planes of rutile (200), rutile (002) and anatase (211), whereas film grown at 500 Î¿C resulted in a crystal plane of rutile (002) with columnar grain and surface morphology relatively smooth. On the other hand, film grown at temperature of 550 Î¿C has rutile (200) and rutile (002) planes. The surface morphology of thin films TiO2:Eu was affected by Eu atom concentration. The roughness of surface morphology increased with increasing Eu content and therefore the grains became larger. It can be concluded that the crystal structure and surface morphology properties of the films depended significantly on the substrate temperature.